Identification of Methanyl yellow and Rhodamin B content in ready-to-serve lidi noodles - Solikah, Jainab Putri; Khoiron, Khoiron; Nurika, Globila (Universitas Nahdlatul Ulama Surabaya, 2025)
Methanyl Yellow is a yellow synthetic dye with the molecular formula C₁₈H₁₄N₃NₐO₃S and a molecular weight of 3.4 gr/mol. Rhodamine B is a dangerous dye with the molecular formula C₂₈H₃₁N₂O₃Cl. Its effects cause respiratory problems, eye irritation, low blood pressure, bladder cancer, diarrhea, nausea, vomiting, kidney, lymphatic and liver damage. The purpose of this study was to describe the presence and absence of methanyl yellow and rhodamin B content in ready-to-eat stick noodles registered as Household Industry Food at the Jember Regency Health Office. This type of research is descriptive quantitative by taking samples from 4 Household Industries ready-to-eat stick noodles in Jember Regency and using laboratory tests to determine the content of Methanyl Yellow and Rhodamin B. The population of this study were all ready-to-eat stick noodles. The population of this study were all ready-to-eat stick noodles of different flavors taken using total sampling technique for samples of stick noodles without seasoning, and for seasoning samples using purposive sampling technique according to the inclusion criteria, namely ready-to-eat stick noodles registered as household industry food, ready-to-eat stick noodles that use yellow and red seasonings. The results of the test for Methanyl Yellow in 4 samples of unseasoned pasta were negative. The results of the Methanyl Yellow test on 4 samples of ready-to-eat yellow stick noodle seasoning were negative. In addition, rhodamin B testing on 20 samples of ready-to-eat red stick noodle seasoning was also negative. The conclusion of this study is that there is no Methanyl Yellow and Rhodamin B content in ready-to-eat stick noodles registered as Household Industry Food in Jember Regency.